2019
DOI: 10.1002/hed.25436
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of oropharyngeal cancers mediated by oral human papillomavirus infection: Results from a Canadian study

Abstract: Background This study aimed to estimate the extent to which oral sex behavior is associated with an increased risk of oropharyngeal cancers (OPCs), and how much of the association is mediated by oral human papillomavirus (HPV) infection. Methods We used data from a hospital‐based case‐control study conducted in Montreal, Canada. Information on oral sex behaviors was collected. Oral rinse and oral brush specimens were analyzed for HPV positivity and genotyping. Logistic regression estimated the odds ratios (OR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The patients with HPVpositive HNSCCs tended to be younger, white, men, and individuals with local T category and poorly differentiated tumors (Li et al, 2018). Sexual behaviors such as oral sex practice and having multiple lifetime number of oral or genital sexual partners were associated with these cases (Emmett et al, 2018;Laprise et al, 2019). Regarding the prognosis, a significantly better survival and treatment response were observed among those with HPV infection (Li et al, 2018;Tian et al, 2019).…”
Section: Human Papillomavirus 16 and 18 Infection In Oral Cancer In Tmentioning
confidence: 99%
“…The patients with HPVpositive HNSCCs tended to be younger, white, men, and individuals with local T category and poorly differentiated tumors (Li et al, 2018). Sexual behaviors such as oral sex practice and having multiple lifetime number of oral or genital sexual partners were associated with these cases (Emmett et al, 2018;Laprise et al, 2019). Regarding the prognosis, a significantly better survival and treatment response were observed among those with HPV infection (Li et al, 2018;Tian et al, 2019).…”
Section: Human Papillomavirus 16 and 18 Infection In Oral Cancer In Tmentioning
confidence: 99%
“…3 Case-control studies have demonstrated strong associations between sexual behaviors and odds of HPV-related OPC (HPV-OPC). [4][5][6][7][8][9] However, these studies focused primarily on number of sexual partners without other contextual data about relationship dynamics, intensity of exposure, or order of acts at sexual debut.…”
Section: Introductionmentioning
confidence: 99%
“…Human papillomavirus (HPV) has driven an increase in incidence of oropharyngeal cancer (OPC) in the United States and other countries, 1,2 which is thought to be explained by trends in oral sexual behavior 3 . Case‐control studies have demonstrated strong associations between sexual behaviors and odds of HPV‐related OPC (HPV‐OPC) 4‐9 . However, these studies focused primarily on number of sexual partners without other contextual data about relationship dynamics, intensity of exposure, or order of acts at sexual debut.…”
Section: Introductionmentioning
confidence: 99%
“…Classical risk factors for HNSCC include tobacco and alcohol consumption. However, more recently, a surge in human papilloma virus (HPV)-associated oropharyngeal cancers have been reported in the US, 1 Canada 2 and UK. 3 These cancers are also affecting a much younger population without classical risk factors for HNSCC.…”
Section: Introductionmentioning
confidence: 99%